Senegal : Sixth Review Under the Policy Support Instrument and Request for Modification of an Assessment Criterion-Staff Report; Informational Annex; Press Release and Executive Director's Statement. (IMF Staff Country Reports; Country Report, 2014)
The Article IV consultation with Senegal was completed by the Executive Board on December 10, 2012. In concluding the 2012 Article IV consultation, executive directors commended Senegal's satisfactory program implementation despite the challenging internal and external environments. They stressed that although a moderate pickup in growth is expected in the near term, the economy remains exposed to substantial risks. Directors welcomed the authorities' continued commitment to their program to ensure macroeconomic stability, strengthen the economy's resilience to shocks, foster higher and sustainable growth, and reduce poverty. Directors noted that, while Senegal still faces a low risk of debt distress, high fiscal deficits and rising debt ratios need to be addressed.